Causality and Subjectivity in Spanish Connectives: Exploring the Use of Automatic Subjectivity Analyses in Various Text Types - Andrea Santana; Dorien Nieuwenhuijsen; Wilbert Spooren; Ted Sanders (Discours)
Causality and subjectivity are relevant cognitive principles in the categorization of coherence relations and connectives. Studies in various languages have shown how both notions can explain the meaning and use of different connectives. However, the Spanish language has been understudied from this perspective. Also, most of the existing research on connectives has used manual analyses. This paper explores the use of automatic analyses of subjectivity in causal connectives. The goal is to determine the degree to which Spanish causal connectives encode subjectivity across different text types, by carrying out automatic analyses. A corpus was constructed to identify causal connectives in journalistic texts (news and editorials) and academic texts (essays, research articles and textbooks in education and psychology). A Spanish lexicon of subjectivity was used to automatically identify the frequency of subjective words in the texts and the segments linked by the most frequent causal connectives. Our assumption is that supposedly subjective connectives will occur in more subjective environments, that is, a context containing relatively many subjective words. The results show a statistically significant relationship between the use of connectives and text type, and also between the text type and subjectivity. From a methodological point of view, the use of automatic analyses appears not to be without difficulties. However, it allowed us to explore various text types, to analyze the degrees of subjectivity in each of them and to identify tendencies related to the use of connectives in Spanish. More interestingly, the combination of automatic and manual analyses can result in a promising methodology for the study of discourse coherence and connectives.